1992
DOI: 10.1136/jmg.29.6.432
|View full text |Cite
|
Sign up to set email alerts
|

Terminal 22q deletion associated with a partial deficiency of arylsulphatase A.

Abstract: A 7 month old girl with psychomotor retardation, hypotonia, and minor malformations was found to have a terminal deletion of the long arm of chromosome 22, del(22)(ql3.31). The partial deficiency of arylsulphatase A (ARSA) and the normal level of NADH diaphorase 1 (DIAl) suggests that the ARSA locus can be regionally assigned to 22q13.31-+qter and the DIAl locus can be excluded from the same segment. This report is the third published case with a terminal 22q deletion.Partial monosomy 22 has been reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…The result of FISH analysis and normal activity of arylsulfatase A in the lymphocytes, the gene of which is mapped to chromosome 22q13.3 [Geurts van Kessel et al, 1980;Narahara et al, 1992] indicate that a 22q13.3 segment is not deleted in her chromosome. Among the 18 previously reported patients with 22q13 (22)(q13.1q13.2) and Accelerated Growthdeletion [Herman et al, 1988;Romain et al, 1990;Zwaigenbaum et al, 1990;Narahara et al, 1992;Phelan et al, 1992;Nesslinger et al, 1994;Dohney et al, 1997;Wong et al, 1997;Schröder et al, 1998], there has been only one patient who had an interstitial deletion of a 22q13 segment [Romain et al, 1990] and no case of interstitial deletion involving a 22q13.1-q13.2 segment, as seen in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of FISH analysis and normal activity of arylsulfatase A in the lymphocytes, the gene of which is mapped to chromosome 22q13.3 [Geurts van Kessel et al, 1980;Narahara et al, 1992] indicate that a 22q13.3 segment is not deleted in her chromosome. Among the 18 previously reported patients with 22q13 (22)(q13.1q13.2) and Accelerated Growthdeletion [Herman et al, 1988;Romain et al, 1990;Zwaigenbaum et al, 1990;Narahara et al, 1992;Phelan et al, 1992;Nesslinger et al, 1994;Dohney et al, 1997;Wong et al, 1997;Schröder et al, 1998], there has been only one patient who had an interstitial deletion of a 22q13 segment [Romain et al, 1990] and no case of interstitial deletion involving a 22q13.1-q13.2 segment, as seen in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, deletion of 22q13 band has been reported in only 18 patients [Herman et al, 1988;Romain et al, 1990;Zwaigenbaum et al, 1990;Narahara et al, 1992;Phelan et al, 1992;Nesslinger et al, 1994;Dohney et al, 1997;Wong et al, 1997;Schröder et al, 1998]. All of them were a terminal deletion involving 22q13, but only one had interstitial deletion of this segment [Romain et al, 1990].…”
Section: Introductionmentioning
confidence: 88%
“…Intellectual impairment, hypotonia, normal to accelerated growth, absent to severely delayed speech, and minor dysmorphic features emerged as common characteristics of individuals with deletion of 22q13.3 [Watt et al, 1985;Kirshenbaum et al, 1988;Romain et al, 1990;Zwaigenbaum et al, 1990;Narahara et al, 1992]. Nesslinger et al [1994] first suggested that this was the recognizable phenotype of deletion 22q13.3, and they narrowed the critical region of overlap from a proximal breakpoint below D22S97 to a region distal to ARSA , a distance of less than 25.5 cM.…”
mentioning
confidence: 99%
“…2. Simple deletions detected at routine banded chromosome examination, with or withouth subsequent con®rmation by FISH or molecular marker studies (Herman et al, 1988;Kirshenbaum et al, 1988;Zwaigenbaum et al, 1990;Narahara et al, 1992;Phelan et al, 1992;Nesslinger et al, 1994;Wong et al, 1997;Yong et al, 1997;Schro È der et al, 1998); this deletion of a part of 22q13 is associated with a common phenotype of mild dysmorphisms, normal or accelerated growth, muscular hypotonia, defective or even absent speech, and mental de®ciency of moderate degree. Since the latter ®nding was reported in all evaluated patients, it has already been suggested that a gene or genes controlling the development of expressive speech maps within 130 kb off the telomere of 22q (Wong et al, 1997;Precht et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Although distal 22q deletions have been well documented postnatally (Watt et al, 1985;Romain et al, 1990;Zwaigenbaum et al, 1990;Narahara et al, 1992;Phelan et al, 1992;Nesslinger et al, 1994;Flint et al, 1995;Ning et al, 1996;Doheny et al, 1997;Slavotinek et al, 1997;Yong et al, 1997;Herman et al, 1988;Precht et al, 1998;Schro È der et al, 1998), prenatal diagnosis of this abnormality, particularly in the mosaic form, has not been reported as yet. We describe what we believe to be the ®rst case of prenatal diagnosis of mosaicism for a del(22)(q13) in a fetus, associated with anomalies on ultrasound.…”
Section: Introductionmentioning
confidence: 94%